Quand la pratique lexicographique se modernise en RD Congo. Note sur Nkòngamyakù Cilubà–Mfwàlànsa, dictionnaire bilingue de NgoSemzara Kabuta - Crispin Maalu-Bungi (Woordeboek van die Afrikaanse Taal-WAT, 2012)
Ciluba is one of the four national Congolese languages spoken in the central south of the country. Since the end of the 19th century, it has acquired the status of a written language and up to the present possesses several lexicographic works of which the first, dating from 1881, is a Ciluba–German vocabulary compiled by a German explorer. Nkòngamyakù Cilubà–Mfwàlànsa is a bilingual dictionary developed by NgoSemzara Kabuta, professor of African linguistics and literature at the University of Ghent, with the triple aim of complementing and filling the gaps of the last dictionary in this genre published in 1960 by a Catholic priest, giving an account of the evolution of the language and proposing the standard form for Ciluba so that it could be used in institutional communication, especially in education. Compared with the works of predecessors, missionaries and regional officials, this new reference tool brings several innovations, mainly: the provision of a dictionary in electronic format and paper, the increase of the number of entries from 10 000 to 16 000, the use of a simple, practical and effective orthography likely to help with reading when learning the language, the significant number of parameters and justifications for each entry to make comprehension easier, the addition of a minigrammar, wholly in Ciluba, a way of contributing to the development, promotion and enriching of this language, particularly through grammatical terminology. In spite of the errors owing to its innovative character, this lexicographic work whose merit is, in various respects, unquestionable, is an answer to the call recently made to African, especially Bantu lexicographers for more comprehensive works.